Comparison of IrO2@FeVS and IrO2@Co-FeVS catalysts in PEM electrolysis at different temperatures - Cokyasa, Mine; Baytar, Orhan; Sahin, Omer; Ekinci, Arzu (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
In this study, FeVS and Co-FeVS nanoparticles synthesized via a hydrothermal method using sunflower shell extract were employed as support materials for IrO2 catalysts prepared by the Adams method. The resulting IrO2@FeVS and IrO2@Co-FeVS catalysts were calcined at various temperatures (500-800 degrees C) and evaluated as anode catalysts in the proton exchange membrane electrolyzer cell (PEMEC). The catalysts calcined at 500 degrees C were further examined at operating temperatures between 20 and 70 degrees C. The results showed that increasing the operating temperature enhanced proton conductivity and reaction kinetics, thereby reducing the cell voltage; the optimum performance was achieved at 70 degrees C. In terms of calcination temperature, the best electrochemical activity was obtained for catalysts treated at 500-600 degrees C, while higher temperatures (700-800 degrees C) led to performance loss due to particle growth and reduced surface area. Structural analyses confirmed uniform dispersion of IrO2 on the FeVS support. Co incorporation decreased crystallite size, improved electrical conductivity, and enhanced interfacial stability, resulting in superior catalytic performance. Overall, the optimum PEMEC performance was achieved at 500-600 degrees C calcination and 70 degrees C operating temperature, yielding high current densities at lower voltages. The optimal conditions for PEMEC operation were determined to be a calcination temperature of 500-600 degrees C and a cell operating temperature of 70 degrees C. Under these conditions, high current densities were achieved at lower cell voltages, indicating improved catalytic efficiency at elevated temperatures.
Keywords: Green synthesis; FeVS; IrO 2 catalyst; PEM electrolyzer; Calcination temperature; Anode catalyst; Electrochemical performance; OXYGEN EVOLUTION; ACIDIC WATER; ELECTROCATALYSTS; NANOPARTICLES; IRO2; OER; Chemistry; Electrochemistry; Energy & Fuels